Isotopic analysis of modern sorghum and finger millet from different altitudes in Ethiopia: implications for ancient farming practices - Varalli, Alessandra; Beldados, Alemseged; D'Agostini, Francesca; Mvimi, Malebogo; D'Andrea, Catherine; Lancelotti, Carla (Frontiers in Environmental Archaeology, 2024)
C4 crops such as sorghum (Sorghum bicolor) and finger millet (Eleusine coracana) have played a significant role in the economic livelihood in arid and semi-arid zones of tropical and sub-tropical Africa since prehistoric times. However, to date, our knowledge of their past management practices is limited. Stable isotope analysis of archaeobotanical remains has been recognised as a valuable tool for reconstructing past agricultural practices, e.g. water management, and fertilization. Nonetheless, our limited understanding of the isotopic variability of C4 plants calls for further research on modern plant before application to archaeobotanical remains. In this paper, we aim to enhance our understanding of modern C4 botanical remains’ isotopic variability by analysing sorghum and finger millet plants. These crops were cultivated according to traditional local practices and collected from ten villages located in the Konso Zone (South Ethiopia) and Tigray Regional State (North Ethiopia), where they are among the daily ingredients for food, and traditional alcoholic and non-alcoholic drinks. We analysed carbon and nitrogen stable isotopes of seeds and biosilica content in chaff, as it has been suggested that a relationship can exist between silicon and C:N. Carbon isotope values show significant variability, positively correlated with altitude. By demonstrating the sensitivity of C4 grain carbon stable isotope to altitude variations, which are likely connected to water availability, this study offers invaluable insights for the accurate assessment of isotopic values derived from ancient C4 crops. The absence of significant correlations with δ15N suggests that nitrogen isotope values may be less effective for understanding environmental variations in this kind of context. This highlights the limitations of nitrogen isotope data for interpreting ancient agricultural practices and underscores the importance of relying more on carbon isotopes for insights related to environmental conditions and altitude. Furthermore, we confirm that the amount of assimilated carbon may depend also on the biosilica content, which is in turn modulated by environmental parameters such as water availability or soil silicon levels.